Advances into Understanding the Vital Role of the Mitochondrial Citrate Carrier (CIC) in Metabolic Diseases. (November 2020) - Peng, Ruyi; Zhang, Meng; Wang, Haizhou; Lin, Jun; Wang, Hongling; Wang, Fan; Liu, Lan; Zhao, Qiu; Liu, Jing
Graphical abstract: Highlights: Mutations or abnormal expression of CIC were involved in multiple diseases. CIC is believed to be a key player and might serve as a novel therapeutic target in types of human metabolic diseases. The structure and function of CIC, CIC related diseases as well as the potential molecular mechanisms were detailedly described. Abstract: The mitochondrial citrate carrier (CIC) is a nuclear-encoded protein located in the inner mitochondrial membrane. By mediating efflux of citrate from the mitochondria to the cytosol, CIC links mitochondrial central carbon metabolism and cytosolic lipogenesis together. Abnormal activity or expression of CIC was found in cancers, developmental disorders and many other diseases. Recently, the specific inhibitors of CIC were proved to modify basic cellular metabolism, which in turn led to changes in disease course such as reverted steatohepatitis and cancer cell death. CIC is believed to be a key player and may serve as a novel therapeutic target in types of human metabolic diseases. Therefore, in this paper, we integrally described the structure and function of CIC. Then, we gave an overview of CIC related diseases including cancers, congenital diseases, pro-inflammatory effects and some other diseases. At the same time, the potential molecular mechanisms of CIC in the above diseases were illuminated. Finally, we illuminated some emerging areas for future investigation.